Mortality risk and social network position in resident killer whales: sex differences and the importance of resource abundance. Issue 1865 (25th October 2017) - Ellis, S.; Franks, D. W.; Nattrass, S.; Cant, M. A.; Weiss, M. N.; Giles, D.; Balcomb, K. C.; Croft, D. P.
Abstract : An individual's ecological environment affects their mortality risk, which in turn has fundamental consequences for life-history evolution. In many species, social relationships are likely to be an important component of an individual's environment, and therefore their mortality risk. Here, we examine the relationship between social position and mortality risk in resident killer whales ( Orcinus orca ) using over three decades of social and demographic data. We find that the social position of male, but not female, killer whales in their social unit predicts their mortality risk. More socially integrated males have a significantly lower risk of mortality than socially peripheral males, particularly in years of low prey abundance, suggesting that social position mediates access to resources. Male killer whales are larger and require more resources than females, increasing their vulnerability to starvation in years of low salmon abundance. More socially integrated males are likely to have better access to social information and food-sharing opportunities which may enhance their survival in years of low salmon abundance. Our results show that observable variation in the social environment is linked to variation in mortality risk, and highlight how sex differences in social effects on survival may be linked to sex differences in life-history evolution.